2007
DOI: 10.1016/j.gene.2007.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the histone nuclear factor P (HiNF-P) gene by HiNF-P and its cyclin E/CDK2 responsive co-factor p220NPAT defines a novel autoregulatory loop at the G1/S phase transition

Abstract: Histone nuclear factor P (HiNF-P) activates histone H4 gene transcription at the G1/S phase transition upon association with its cyclin E/CDK2 responsive co-factor p220 NPAT . Here we characterize the gene regulatory pathways that control the proliferation-related expression of HiNF-P. The HiNF-P locus contains a single TATA-less 0.6 kbp promoter with multiple phylogenetically conserved transcription factor recognition motifs. Transient reporter gene assays with HiNF-P promoter deletions show that there are at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…NPAT, along with HINFP, resides in subnuclear domains designated histone locus bodies (HLBs), where both histone gene transcription machinery and regulators of 3=-end processing of primary histone transcripts colocalize with histone genes (23)(24)(25)(26)(27). The HINFP-NPAT complex mediates a unique cell cycle regulatory mechanism that controls the G 1 /S-phase transition (9,18,19,(28)(29)(30) and operates independently of the classical restriction point-related E2F/pRB switch. The biological significance of HINFP-mediated loss of histone H4 in cell cycle control is reflected by our earlier findings that a constitutive null mutation of the mouse Hinfp gene causes early embryonic lethality (31).…”
mentioning
confidence: 99%
“…NPAT, along with HINFP, resides in subnuclear domains designated histone locus bodies (HLBs), where both histone gene transcription machinery and regulators of 3=-end processing of primary histone transcripts colocalize with histone genes (23)(24)(25)(26)(27). The HINFP-NPAT complex mediates a unique cell cycle regulatory mechanism that controls the G 1 /S-phase transition (9,18,19,(28)(29)(30) and operates independently of the classical restriction point-related E2F/pRB switch. The biological significance of HINFP-mediated loss of histone H4 in cell cycle control is reflected by our earlier findings that a constitutive null mutation of the mouse Hinfp gene causes early embryonic lethality (31).…”
mentioning
confidence: 99%
“…[14][15][16][17][18] The HINFP-NPAT complex regulates expression of histone genes during the G1/S phase and entry into S phase. [9][10][11][19][20][21] Our recent findings indicated that Hinfp-mediated control of histone H4 gene expression during S phase is essential for cell growth and proliferation. [22][23][24] Complete ablation of Hinfp in mice causes early embryonic lethality between embryonic day (E) 3.5 and E6.5.…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle controlled transcription of histone H4 genes, as well as other core histone proteins (e.g., H2A, H2B and H3) at HLBs is a key step. This step is initiated in part by the cyclin E/ CDK2 dependent phosphorylation of the p220 NPAT / HINFP complex at the G1/S phase transition (Holmes et al, 2005; Le et al, 2006; Ma et al, 2000; Medina et al, 2006; Medina et al, 2007; Medina et al, 2008; Miele et al, 2005; Mitra et al, 2003; Mitra et al, 2007; Mitra et al, 2009; van Wijnen et al, 1992; Wei et al, 2003; Xie et al, 2007; Ye et al, 2003; Zhao et al, 2000). Activation of DNA damage repair pathways and cell cycle arrest block the transcriptional activation of histone H4 genes by p220 NPAT and HINFP (Mitra et al, 2009; Pirngruber and Johnsen, 2010; Su et al, 2004).…”
Section: Introductionmentioning
confidence: 99%